Paucimannose-Rich N-glycosylation of Spatiotemporally Regulated Human Neutrophil Elastase Modulates Its Immune Functions - Loke, Ian (Mol Cell Proteomics, 2017)
Human neutrophil elastase (HNE) is an important N-glycosylated serine protease in the innate immune system, but the structure and immune-modulating functions of HNE N-glycosylation remain undescribed. Herein, LC-MS/MS-based glycan, glycopeptide and glycoprotein profiling were utilized to first determine the heterogeneous N-glycosylation of HNE purified from neutrophil lysates and then from isolated neutrophil granules of healthy individuals. The spatiotemporal expression of HNE during neutrophil activation and the biological importance of its N-glycosylation were also investigated using immunoblotting, cell surface capture, native MS, receptor interaction, protease inhibition, and bacteria growth assays. Site-specific HNE glycoprofiling demonstrated that unusual paucimannosidic N-glycans, particularly Manα1,6Manβ1,4GlcNAcβ1,4(Fucα1,6)GlcNAcβ, predominantly occupied Asn124 and Asn173. The equally unusual core fucosylated monoantenna complex-type N-sialoglycans also decorated these two fully occupied sites. In contrast, the mostly unoccupied Asn88 carried nonfucosylated paucimannosidic N-glycans probably resulting from low glycosylation site solvent accessibility. Asn185 was not glycosylated. Subcellular- and site-specific glycoprofiling showed highly uniform N-glycosylation of HNE residing in distinct neutrophil compartments. Stimulation-induced cell surface mobilization demonstrated a spatiotemporal regulation, but not cell surface-specific glycosylation signatures, of HNE in activated human neutrophils. The three glycosylation sites of HNE were located distal to the active site indicating glycan functions other than interference with HNE enzyme activity. Functionally, the paucimannosidic HNE glycoforms displayed preferential binding to human mannose binding lectin compared with the HNE sialoglycoforms, suggesting a glycoform-dependent involvement of HNE in complement activation. The heavily N-glycosylated HNE protease inhibitor, α1-antitrypsin, displayed concentration-dependent complex formation and preferred glycoform-glycoform interactions with HNE. Finally, both enzymatically active HNE and isolated HNE N-glycans demonstrated low micromolar concentration-dependent growth inhibition of clinically-relevant Pseudomonas aeruginosa, suggesting some bacteriostatic activity is conferred by the HNE N-glycans. Taken together, these observations support that the unusual HNE N-glycosylation, here reported for the first time, is involved in modulating multiple immune functions central to inflammation and infection.